RHD*weak partial 4.0 is associated with an altered RHCE*ce(48C, 105T, 733G, 744C, 1025T) allele in the Tunisian population. Issue 4 (7th June 2013) - Ouchari, M.; Polin, H.; Romdhane, H.; Abdelkefi, S.; Houissa, B.; Chakroun, T.; Gabriel, C.; Hmida, S.; Jemni Yacoub, S.
Summary Background and Objectives D is the most immunogenic blood group antigen. About 1% of whites carry an altered RHD allele leading to quantitative or qualitative changes in the antigen D expression. T201R and F223V encoded by 602C>G and 667T>G are specific amino acid substitutions of the weak D type 4 cluster of African origin, comprising the alleles RHD*09.01, RHD*09.02, RHD*09.03, RHD*09.04 and RHD*09.05. The purpose of this study was to estimate the presence of these RHD genotypes in the Tunisian population. Materials and Methods Ethylenediaminetetraacetate blood samples from 907 D+ and 93 D− blood donors were tested for markers 602G and 667G by allele‐specific primer‐polymerase chain reaction (PCR‐ASP). Samples with positive reactions were re‐evaluated by DNA sequencing for RHD and RHCE exons 1–10 and adjacent intronic sequences. Results Among 907 D+ samples, 19 individuals were identified to harbour the RHD*weak partial 4.0 allele. RHCE sequencing post‐haplotype‐specific extraction (HSE) revealed an altered RHCE*ce(48C, 105T, 733G, 744C, 1025T) in those samples. The linkage of the RHCE polymorphisms to one haplotype was proven by DNA sequencing post‐HSE. Conclusion The RHD*weak partial 4.0 allele syn. RHD*09.03 was estimated to occur 1 in 47 among D+ Tunisians. There was no evidence for other RHD alleles included in the weak D type 4 cluster.